Mereproduksi Inti Model Pembelajaran di Madrasah Suatu Pembersihan dari Konsep Liberalisasi Pendidikan Islam abad ke-21 - Hasan H.A. Buro (PROGRESSA: Journal of Islamic Religious Instruction, 2019)
Modern academic trends towards specialties that see 'education' as a separate study area and limit the study of Islamic education, both for theological research, historiological narratives, or research on social injustice, such generalizations are problematic at the level of difficulty faced, when talking about 'face of civilization' in education, even though the accuracy of such generalizations is questionable, but they still exist as useful types of ideal education that are forged in a (unique) worldview, and in this sense we accept the term 'Islamic education,' although in practice, everything is different, most madrassas are like ordinary business, For many of them controlling the madrasa is only a means of advancing personal, material, and political interests, where they are willing to use 'any acceptable and unacceptable way'. The question of this article is how to reproduce the core core model of learning in the madrasa, a purge of the concept of liberalization of 21st century Islamic education ?. From the results of the discussion it was concluded: 1) modern educators who studied Islamic education initially experienced difficulties and differentiation that seemed tiring, becoming a meaningful and dynamic whole in the madrasa's daily routine, the teachers helped students "manifest" the Qur'an in their hearts with confidence that it leads us to properly understand the spirit of its messages, which in turn will guide them in every aspect of their lives. 2) the curriculum in the Qur'an follows a holistic approach that contrasts with a banking system in which educators store information into students' memories for safekeeping. Learning takes place through the interaction between students and the environment in a democratic and integral class that continues to reflect themselves and the world, building authentic forms of thought and action. 3) People can choose the field of study they want in accordance with the needs or demands of the market, but seeking knowledge is a basic mandate in the curriculum with a Qur'anic background